Efficacy of inguinal buffered lidocaine and intranasal flunixin meglumine on mitigating physiological and behavioral responses to pain in castrated piglets - Lopez-Soriano, Magdiel; Merenda, Victoria Rocha; Anderson, Stephanie; Trindade, Pedro Henrique Esteves; Leidig, Martin S.; Messenger, Kristen; Ferreira, Juliana Bonin; Pairis-Garcia, Monique Danielle (Frontiers in Pain Research, 2023)
Managing castration pain on US sow farms is hindered by the lack of Food and Drug Administration (FDA) approved products for mitigating pain. Previous work assessing flunixin meglumine (FM) efficacy in mitigating castration pain has shown the drug to be effective in pigs, meanwhile, results from previous work evaluating lidocaine efficacy are contradictory. Therefore, the objectives of this study were to determine the efficacy of inguinal buffered lidocaine (BL) and FM in mitigating castration pain in piglets. This study was divided into Part I (physiological response) and Part II (behavioral response). For part I piglets were randomly assigned to the following treatments: T1: (C) Castration plus physiological saline; T2: (S) Sham plus physiological saline; T3: (CL) Castration plus BL; T4: (SL) Sham plus BL; T5: (CF) Castration plus FM; T6: (SF) Sham plus FM; T7: (CLF) Castration plus BL and FM; T8: (SLF) Sham plus BL and FM. Blood was collected 24h prior to castration, 1h, and 24h post castration for cortisol quantification. For Part II another cohort of piglets was enrolled and randomly assign to the following treatments: T1: (C) Castration plus physiological saline and T7: (CLF) Castration plus BL and FM. Behavior scoring was obtained in real-time by observing each piglet for 4-min continuously using Unesp-Botucatu pig acute pain scale (UPAPS) at the following timepoints: 1h before castration (-1h), immediately post-castration (0h), and 3h post-castration (+3h). Average cortisol concentrations did not differ at -24h (P>0.05) or at 24h post-castration (P>0.05) between treatments. At 1h post-castration, castrated piglets (C and CL) demonstrated greater cortisol concentrations. Castrated piglets in the CF and CLF group had lower cortisol concentrations compared to C and CL-treated pigs (P<0.05). For behavioral response, there were no differences between treatments on total UPAPS scores (C and CLF, P >0.05). Intranasal FM was able to effectively reduce the physiological piglet’s response immediately post-castration. Inguinal buffered lidocaine had no effect on the either physiological or behavioral response to pain. Long-term research should focus on refining injection techniques for inguinal BL and consider administration frequency and dosing of intranasal FM to control pain for a longer period post-castration.